The Effect of Transformational Leadership Style and Job Satisfaction on Employee Performance Mediated by Intrinsic Motivation (Study on Employees of PT Bisma Aero Sejahtera) - Frankie Franciscus Mamahit; Christian Haposan Pangaribuan (PT. Publikasiku Academic Solution, 2024)
The application of transformational leadership style in an organisation is one of the strategies to improve employee performance. Leaders with transformational leadership style are able to bring the organisation to a better direction by inspiring and supporting the development of employee potential to achieve the vision. One of the other important factors that can affect employee performance is job satisfaction. Job satisfaction is the general attitude of an individual towards their work. However, the relationship between transformational leadership, job satisfaction, and employee performance sometimes looks ambiguous and inconsistent, so mediating variables are needed to strengthen and clarify the relationship between transformational leadership style, job satisfaction, and employee performance. Intrinsic motivation in this case can act as a mediator that connects between transformational leadership style, job satisfaction and employee performance. The purpose of this research is to see and analyse the influence between one variable to another that affects the performance of employees. The variables to be examined in this study are transformational leadership, job satisfaction, employee performance and intrinsic motivation as a mediating variable. The research method used in this research is quantitative. This study uses a questionnaire approach as a data collection tool that is distributed via an online questionnaire to employees of PT Bisma Aero Sejahtera. The research limitations in this study are that the survey was only conducted on employees of PT Bisma Aero Sejahtera located at the Garuda Maintenance Facility (GMF) Cengkareng, Soekarno-Hatta airport area and the period of this survey was only conducted within a span of one month.